Empirical Assessment of China’s outward foreign direct Investment to Africa - Nketiah, Emmanuel; Adjei, Mavis; Obuobi, Bright; Adu-Gyamfi, Gibbson (International Journal of Advanced Engineering Research and Science, 2020)
China's economy's progress and relations with other developing countries have received much attention, particularly how Sino-African relations have evolved since 2000. However, China's foreign direct investment (FDI) on economic development in Africa requires empirical assessment. This study investigates the causal effect relationship between GDP and China's outward FDI in Africa from 2003-2018 using panel data analysis. Contrary to the limited existing literature in Africa, an advanced econometric approach such as dynamic panel data estimation isused to ascertain the effect of China’s exports to Africa, China’s imports from Africa,Gross Annual Revenues of Chinese Companies' Construction Projects in Africa, and China's outward FDI to Africa. Our results suggest that China's outward FDI to Africa exerts a positive and significant impact on GDP. Moreover, there is a positive relationship between China's exports to Africa, China's imports from Africa,Gross Annual Revenues of Chinese Companies' Construction Projects in Africa, and GDP. The causal effect finds a short-term relationship between GDP and China’s outward FDIto Africa.The results show a strong implication in 39 Africa countries. More precisely, China's outward foreign direct investment in Africa and the Gross Annual Revenues of Chinese Companies' Construction Projects in Africa will surely have positive effects on the GDP (current US) and the country’s economic growth.Thus, the study recommends implementing measures and policies to manage China's outward FDIto ensure robust economic development.